(untitled) (World Economics and Finance Bulletin, 2023)
This article explores the critical role that management decisions play in attracting investment projects. It examines the impact of strategic choices, risk management, and effective leadership in creating an environment conducive to attracting investments. The study employs a qualitative approach, analyzing case studies and industry examples to illustrate the correlation between managerial decisions and successful investment attraction.